Implementing Reflective Practice in English Language Learning: Teachers’ and Pre-Service Teachers’ Perceptions - Seyna Putri Suswanto; Zulfa Sakhiyya (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study investigates the application of reflective practice in English language teaching in Indonesia by analyzing the perceptions of in-service and pre-service teachers. Data were collected through an online survey of 31 respondents across educational levels. Results indicate that reflective practice is widely regarded as essential for the ongoing evaluation and improvement of teaching strategies. Academic literature emerged as the primary source of insight, supplemented by training, personal experience, and peer discussions. Teachers reported varying frequencies of reflection, with most engaging occasionally, while time constraints, limited training, and challenges in assessing impact hinder consistent implementation. Drawing on Schön’s (1983) concepts of reflection-in-action and reflection-on-action, the study highlights the need to embed reflective practice more systematically within curriculum design and professional development programs. The findings underscore the importance of longitudinal research to further examine how reflective strategies can be sustained and institutionalized in teacher education.